DISTRIBUSI PENDAPATAN PETANI KELAPA SAWIT POLA PLASMA DI DESA KERUBUNG JAYA KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Nasidah '; Eliza '; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to know the structure and sources of palm oil farmers’income pattern of plasma in Kerubung Jaya village of Batang Cenaku district of Indragiri Hulu regency, know the distribution and lameness of income the palm oil farmers patern of plasma in Kerubung Jaya village of Batang Cenaku district of Indragiri Hulu regency. The research method used was survey with the sample taken used by Slovinand Proportionalrandom sampling. The sample of research was 87 farmers pattern of plasma. Analysis ofthe data used the Gini Index Ratioand the Lorenz Curve. The results showedthat, farmers’ incomes tructure of the sample consists of the agricultural sector (80.28%) and non-agriculture (19.72%) and the source of the sample farmers' income derived from the principal revenue (oil palm plantations) and there venueside (oil palm non plasma, non official employees, trade, employers, services, and others). Distribution and sample farmers' income in equalityis relatively low (quite evenly), with a ratio Gini index value of 0.15 for oil palm plantations patters of plasma and 0.26 for total income, which both line of Lorenz Curve approaching the diagonal line (line equalization). Keywords:Palm Oil, Kerubung Jaya, The Structure of Income, Income Distribution.